Impact of Service Quality and Price on Customer Satisfaction: A Case Study of Salon Waxinc in Jakarta - Fathonah, Ekayanti Nur (APPS Publications, 2024)
To analyze the impact of service quality and price on customer satisfaction at Salon Waxinc PIK. This study employed a quantitative approach, utilizing purposive sampling of 125 Salon Waxinc PIK customers aged 17-60 who receive treatments at least monthly, and analyzed questionnaire data using Smart-PLS with a Likert scale to examine the relationship between variables. The study’s findings indicate that both service quality and pricing strategies significantly enhance customer satisfaction at Salon Waxinc PIK, suggesting that improvements in service delivery can lead to increased customer loyalty. Additionally, the positive perception of pricing reinforces the importance of aligning pricing strategies with customer expectations to foster repeat business and strengthen the salon’s competitive position in the market. While previous studies have explored the general relationship between service quality, price, and customer satisfaction in the beauty industry, this study distinguishes itself by uniquely examining these factors within the specific context of Salon Waxinc PIK, a niche waxing salon, and specifically within the post-pandemic environment. The research demonstrates that both enhanced service quality, particularly employee performance, and strategic pricing are crucial for driving customer satisfaction in this niche beauty industry.